Evidence for climatic changes around the Matuyama-Brunhes Boundary (MBB) inferred from a multi-proxy palaeoenvironmental study of the GBY#2 core, Jordan River Valley, Israel - Proborukmi, M.; Urban, B.; Mischke, S.; Mienis, H.; Melamed, Y.; Dupont-Nivet, G.; Jourdan, Fred; Goren-Inbar, N. (Elsevier BV, 2017)
© 2017 Elsevier B.V. The Acheulian site of Gesher Benot Ya'aqov (GBY) in the Upper Jordan Valley revealed important data on environment and material culture, as well as evidence for hominin behavioural and cognitive patterns documented at the margins of the Hula Palaeo-lake. A 50m long core (GBY#2) drilled at the archaeological site has provided a long Pleistocene geological, environmental and climatological record, which expands the existing knowledge of hominin-habitat relationships. Bracketed by two basalt flows dated by 40 Ar/ 39 Ar and based on the identification of the Matuyama-Brunhes Boundary (MBB) and correlation with the GBY excavation site, the sedimentary sequence provides the climatic history around the MBB. Multi-proxy data including pollen and non-pollen palynomorphs, macro-botanical remains, molluscs and ostracods provide evidence for lake and lake-margin environments during Marine Isotope Stages (MIS) 20 and 19. Semi-moist conditions were followed by a pronounced dry phase during MIS 20, and warm and moist conditions with Quercus-Pistacia woodlands prevailed during MIS 19. In contrast to the reconstructed climate change from relatively dry to moister conditions, the depositional environment developed from an open-water lake during MIS 20 to a lake margin environment in MIS 19. Generally shallower conditions at the core site in MIS 19 resulted from the progradation of the lake shore due to the filling of the basin. Micro-charcoal analysis suggests a likelihood of human-induced fire in some parts of the core, which can be correlated with artefact-containing layers of the GBY excavation site. The Hula Palaeo-lake region provided an ideal niche for hominins and other vertebrates during global glacial-interglacial climate fluctuations at the end of the Early Pleistocene.